Identification And Development Of Urinary Protein Biomarker To Screen For Kratom Used In Regular Users - Al Suwaychit, Rana Khudhair Jasim (2023)
Study aimed to characterize the urinary protein profile of regular kratom users to determine the impact of kratom on regular use of kratom. Furthermore, to identify a useful urinary biomarker that can be used to indicate kratom dependence and addiction by means of a screening method using ELISA